Universal Church dialogues with other religious practices in southern Mozambique: another Pentecostalism - Fiorotti, Silas (Ilha Revista de Antropologia, 2023)
The paper presents the analysis of some discourses of the Universal Church of the Kingdom of God (UCKG) in southern Mozambique and problematizes the dialogues of this church with aspects of different religious contexts, especially the contexts of “traditional” religious practices and Zione practices. Some elements are emphasized: the mentions of “tradition”; the recognition and appropriation of language, cosmologies and local notions of evil; the phenomenon of possession and exorcism; the phenomenon of sacrifice; the performance of pastors and bishops; and the diagnoses and treatments. The findings show that UCKG’s Pentecostalism differs from other Pentecostalisms present in African contexts, and that several ideas and practices from “traditional” and Zione religious contexts created and create conditions for the UCKG’s discourses and practices to be relevant, effective and significant in southern Mozambique.